Analysis of serum IgE and eosinophils in 80 patients with allergic dermatosis - Yi-xuan LI; Li WANG; Xue-wen HE; Ai-hua HOU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To explore the relationship between serum immunoglobulin E (IgE) and eosinophil (EOS) and different types of allergic skin diseases. Methods: Eighty cases of allergic dermatosis and 80 cases of health examination respectively were enrolled in the observation group and the control group. Fasting venous blood was collected and serum total IgE and EOS levels were measured. The results were compared and analyzed. Results: The levels of serum IgE and EOS in the observation group were significantly higher than those in the control group, and the positive rates of serum IgE and EOS were also significantly higher (P<0.05). There were significant differences in serum IgE level, EOS count, IgE positive rate and EOS positive rate among different types of allergic skin diseases (P<0.05). Serum IgE level, EOS count, IgE positive rate and EOS positive rate were the lowest in allergic purpura group, while they were the highest in eczema group. There was no significant correlation between serum IgE and EOS counts in patients with allergic dermatosis (r=0.16, P>0.05). Conclusion: The occurrence of allergic skin diseases is related to the high expression of serum IgE and EOS. The expression of serum IgE and EOS in different types of allergic skin diseases is significantly different. The clinical treatment plan of immunoglobulin should be reasonably formulated according to the expression characteristics of serum IgE and EOS in allergic skin diseases.